Discontinuation of pregnancy in obstetric practice: therapeutic resource versus provoked abortion - Besio Rollero, Mauricio (Acta Bioethica, 2016)
The issue of induced abortion, in general, and the called therapeutic abortion in particular, has generated a lot of concern for both the medical profession, as well as for all society. They involve important values for individuals and for the entire population. There is much confusion about the terms used to nominate the various actions that the obstetricians decide to implement in clinical situations that their patients present. This paper aims to clarify which pregnancy interruptions are not only permissible but obligatory actions to a doctor, and correspond to the goals of medicine, and which of them are really induced abortions. To do so, the purpose of the medical profession is analyzed and to whom the health professional should always provide their care. Performs a reflection on the difference between concept, criteria, and signs to distinguish them when talking about fetal viability and induced abortion. From that perspective, establishes the concept of induced abortion, seeking its necessary features and avoiding confusion with the criteria and signs used to recognize this reality in a particular case. Finally, follows which are the criteria and signs of a termination of pregnancy in agreement with the values of medicine.